GAMBARAN SAFETY CULTURE PRAMUWISATA DALAM PERTOLONGAN PERTAMA LUKA TRAUMA PADA WISATAWAN ARUNG JERAM SUNGAI AYUNG - Pinarisraya, Ni Putu Ayu Ratih; Suarningsih, Ni Kadek Ayu; Juniartha, I Gusti Ngurah (Coping: Community of Publishing in Nursing; Vol 9 No 2 (2021): April 2021DO - 10.24843/coping.2021.v09.i02.p05, 2021)
White water rafting tourism is a high-risk adventure tour and often causes tourists to experience trauma injuries due to a lack of safety culture. Aim: to know the safety culture of guides in the first aid trauma to the rafting tourists on the Ayung River. Method: this research is a descriptive study of quantitative approach with a cross-sectional method using 140 samples obtained by proportional random sampling technique. Results: based on five characteristics of safety culture, the majority of Ayung River rafting guides have a value of 4 in the great category.Conclusion: the guides can hold on the safety of tourism on rafting.